A study of serum zinc, selenium and copper levels in carcinoma of esophagus patients - Goyal, M. M. (Springer India, 2006)
The association of serum trace elements like selenium, zinc and copper has been found in different types of cancer. This study was conducted to see the serum level of these three trace elements in cancer esophagus patients. Biopsy confirmed cancer esophagus, 24 patients (12 males, 12 females, mean age 54.5±11.65 year with 23 healthy subjects (16 males, 7 females, mean age 44 ±13.82 years) were included in this study. Both control and study group patients were of same socio-economic status and dietary habits. Serum zinc and copper level were estimated using standard absorption spectrometer technique and serum selenium by Hydride generation method. We observed significant low serum levels of zinc and selenium while high level of serum copper in carcinoma esophagus patients, as compared with normal healthy controls. This shows an association of serum selenium zinc and copper with cancer esophagus.